Genetic polymorphism of myostatin (MSTN) in Nigerian sheep breeds (2021)
Myostatin (MSTN) also known as growth differentiation factor 8 (GDF-8) has been implicated to play an important role in growth regulation, and it is a candidate gene in marker assisted selection (MAS). This study was carried out to identify the polymorphism of MSTN gene as a genetic marker for growth traits in Nigerian indigenous sheep. Genomic DNA (gDNA) was extracted from blood samples of Balami, Yankasa, Uda and West African Dwarf (WAD) breeds of sheep. Parts of 5’UTR, intron and exon1 (614bp) was amplified using a primer sequence designed by FastPCR-primer software. The amplicons were digested with restriction enzyme HaeIII and the fragments produced were stained with luminescent dye and run on gel electrophoresis. The genetic structure of the sampled population was investigated after analysis with POPGENE32 software. The HaeIII digested results showed that Myostatin has three polymorphs (AA, AB and BB), controlled by two alleles (A and B), with B having a higher allelic frequency (82.84%) and BB genotype has the highest frequency of 73%. The sampled population showed a deviation from Hardy-Weinberg equilibrium (p<0.05) while the F-statistics results of the Nigerian breeds of sheep showed the breeds are genetically identical (33.40%) within them. The genetic distance matrix established that Uda and Yankasa show the greatest distant (3.00%) while Uda and WAD are almost identical (99.85%). The four breeds of sheep studied showed polymorphism for Myostatin gene in the intron 1 and exon 1. Myostatin, therefore, could be considered a candidate gene for MAS.